2004
DOI: 10.1128/jvi.78.2.630-641.2004
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Recognition of Autologous Virus by High-Avidity CD8 T Cells in Chronic, Progressive Human Immunodeficiency Virus Type 1 Infection

Abstract: CD8 T-cell responses are thought to be crucial for control of viremia in human immunodeficiency virus (HIV) infection but ultimately fail to control viremia in most infected persons. Studies in acute infection have demonstrated strong CD8-mediated selection pressure and evolution of mutations conferring escape from recognition, but the ability of CD8 T-cell responses that persist in late-stage infection to recognize viruses present in vivo has not been determined. Therefore, we studied 24 subjects with advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
115
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 60 publications
9
115
0
2
Order By: Relevance
“…Regardless of all of the efforts spent, there is a certain need to improve current strategies for protective or therapeutic vaccinations against HIV-1. Although high-frequency T cell responses can be observed in HIV-1-infected individuals, even in those with progressing disease (49), there is evidence that virus-specific CD8…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of all of the efforts spent, there is a certain need to improve current strategies for protective or therapeutic vaccinations against HIV-1. Although high-frequency T cell responses can be observed in HIV-1-infected individuals, even in those with progressing disease (49), there is evidence that virus-specific CD8…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to assess multiple parameters of HIV-specific CD8 ϩ T cell responses (19,20). This is in part because although CD8 ϩ T cells can contain HIV replication in some cases (21)(22)(23), ongoing viral replication and disease have also been found in the face of seemingly robust CD8 ϩ T cell responses (24,25). Several studies have found a lack of correlation between IFN-␥ responses and viral load, even using whole HIV proteome screening (26 -28).…”
mentioning
confidence: 99%
“…Several studies have documented very slow escapes and slow sequence evolution during chronic infection (12)(13)(14)(15)(16). The consensus interpretation of these slow takeover rates during chronic infection is that even the dominant CTL clonotypes impose a very minor selection pressure and play a very minor role in controlling the virus (12).…”
mentioning
confidence: 99%
“…All in all, this was taken as evidence suggesting that the virus is largely controlled by other mechanisms during chronic infection (12). However, it is known that CTL responses persist (14,15), and that new CTL responses develop in chronically infected patients (11). Another major aim of this work is to show that the minor selection pressure was to be expected when several CTL clonotypes together control the infection, and, although each of them has very little impact on the control of the infection, they together can play an essential role.…”
mentioning
confidence: 99%